2021
DOI: 10.1088/1674-1056/abb65d
|View full text |Cite
|
Sign up to set email alerts
|

Optical conductivity of twisted bilayer graphene near the magic angle*

Abstract: We theoretically study the band structure and optical conductivity of twisted bilayer graphene (TBG) near the magic angle considering the effects of lattice relaxation. We show that the optical conductivity spectrum is characterized by a series of peaks associated with the van Hove singularities in the band structure, and the peak energies evolve systematically with the twist angle. Lattice relaxation effects in TBG modify its band structure, especially the flat bands, which leads to significant shifts of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…The moiré superlattice in TBG introduces a periodic potential that can enhance the interaction between light and matter, leading to improved light absorption and carrier extraction. [155][156][157][158][159] Xin et al reported photovoltage enhancement in TBG which was achieved by adjusting the twist angle and surface plasmon resonance. The developed photodetector consisted of metal-graphene-metal lay-ers and the results show that the photovoltage intensities depend on the number of graphene layers present and the twist angle.…”
Section: Photovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moiré superlattice in TBG introduces a periodic potential that can enhance the interaction between light and matter, leading to improved light absorption and carrier extraction. [155][156][157][158][159] Xin et al reported photovoltage enhancement in TBG which was achieved by adjusting the twist angle and surface plasmon resonance. The developed photodetector consisted of metal-graphene-metal lay-ers and the results show that the photovoltage intensities depend on the number of graphene layers present and the twist angle.…”
Section: Photovoltaicsmentioning
confidence: 99%
“…The moiré superlattice in TBG introduces a periodic potential that can enhance the interaction between light and matter, leading to improved light absorption and carrier extraction. [ 155–159 ] Xin et al. reported photovoltage enhancement in TBG which was achieved by adjusting the twist angle and surface plasmon resonance.…”
Section: Optoelectronic Applicationsmentioning
confidence: 99%
“…无论是对于TBG还是TBG-hBN体系, 平带 对于这些丰富物理现象的产生都是至关重要的. 除 了用转角来调控平带, 应变也是一种重要的方法, 在样品的制备过程中, 应变的产生几乎是不可避免 的, 比如基底带来的应变作用: 当对两层石墨烯施 加不同的应变时, 其莫尔能带将会受到调制, 原本 非魔角下的TBG在此应变下也能出现平带 [9,10] ; 同时, 应变不仅能够使材料能带拓扑数发生改变 [10] , 也能够使晶格产生重构, 引发许多新奇的物理现象 如孤子 [11] 、光子晶体 [12] 等; 应变相对于转角更易 调控, 只需要具有压电性质的基底即可, 这使得原 位调控范德瓦耳斯材料中的强关联、拓扑以及量子 效应成为可能. 由此可见, 研究应变对于TBG的 影响是在理论和实验上都非常有意义的.…”
Section: 引 言unclassified
“…Optical experiment is a powerful technique to investigate the band structures, many body interactions and various electronic excitations in graphene-based systems [21]. The optical conductivity of TBG has been studied theoretically and experimentally in several previous works [22][23][24][25][26][27][28][29][30]. Earlier theoretical calculations [22][23][24]31] have been done for twist angles θ >= 1.47 • .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier theoretical calculations [22][23][24]31] have been done for twist angles θ >= 1.47 • . More recently, the optical conductivity near the magic angle has been calculated taking into account correlation effects [25] and interlayer tunneling asymmetry [26,27]. So far, the combined effects of heterostrain and lattice * Electronic address: zhiqiangli@scu.edu.cn relaxation on the optical properties of TBG are yet to be explored.…”
Section: Introductionmentioning
confidence: 99%